Effects of Planting Methods on the Establishment, Yield, and Nutritional Composition of Hybrid Grass Cuba OM-22 in the Dry Tropics of Peru - Vásquez, Héctor V. (2025)
Climate change and livestock expansion have affected forage supply in the dry tropics. Therefore, optimizing planting methods adapted to adverse tropical environments is essential for establishment and yield. The objective of this study was to evaluate the effect of different planting methods on the establishment rate, morphology, yield, and nutritional composition of Cuba OM-22 under the soil and climate conditions of the dry tropics of Peru, using a block design with four replicates and five methods for propagation by cuttings. The S4 (two-node cuttings, 25 cm in length; horizontal position 180°, parallel to the soil surface; fully buried at 8 cm depth; no spacing between cuttings along the furrow) method offered the best balance between yield and quality, with higher establishment rate (55.93%), height (182.15 cm; higher than S1 and S5), and more tillers (surpassing S1 and S2 by 16.97% and 18.86%). In addition, it obtained good green forage yields (137.43 t ha⁻¹) and was better than all planting methods in dry matter yield (37.45 t ha⁻¹). In nutritional composition, S4 ranked among the highest averages for nitrogen-free extract (NFE) (43.22%) and ash (11.06%). However, protein, crude fiber, and fat content did not differ between methods. On the other hand, planting methods showed negative correlations between the number of tillers and ash content (p = 0.006; r = −0.79), ash and NFE (p = 0.000; r = −0.92), and protein with crude fiber (p = 0.029; r = −0.68). These findings highlight S4 as a key strategy for optimizing establishment, yield, and quality in Cuba OM-22 in the dry tropics.